Field Methods to Quantify Emergency Responder Fatigue: Lessons Learned from sUAS Deployment at the 2018 Kilauea Volcano Eruption. Issue 3 (2nd July 2020) - Mehta, Ranjana K; Nuamah, Joseph; Peres, S. Camille; Murphy, Robin R.
OCCUPATIONAL APPLICATIONS: There has been increasing use of small unmanned aerial systems in disaster and incident response. We evaluated sUAS pilot states during the tactical response to the 2018 Kilauea Volcano Lower East Rift Zone event, using a 3-minute psychomotor vigilance test (PVT) and wrist worn heart rate sensor. The field data, collected over four days, indicated that the sUAS pilots did not recover to baseline vigilance and physiological levels. Some pilots stopped participating over time, owing to logistical constraints of performing the 3-minute PVT test. Additionally, all pilots refrained from rating their perceived workload levels. We summarize the utility of and challenges associated with collecting performance, physiological, and subjective measures of pilot fatigue during real disaster response. TECHNICAL ABSTRACT: Background: Small unmanned aerial systems (sUAS), which provide remote presence at disasters, are teleoperated by emergency responders who experience elevated fatigue levels exacerbated by disrupted sleep/rest schedule as a mission unfolds. Purpose : We assessed fatigue states of responders who flew sUAS in both day and night missions while assisting with tactical response during the 2018 Kilauea Volcano Lower East Rift Zone event. Methods : We evaluated sUAS pilot states in a real-world disaster response using a 3-minute psychomotor vigilance test and a wrist worn heart rate sensor. Results : The field data, collected over four days, indicated that the sUAS pilots did not recover to baseline vigilance and physiological levels. Conclusions : This is the first study of this kind that evaluated operator states during human-sUAS interaction in a real-world disaster response. Findings here provide critical insights on the challenges and utility of different human factors and ergonomics methods, ranging from performance to physiological and subjective approaches, to capture operator states during high-risk disaster response.